PENGARUH PENGENCERAN ASAM SULFOSALYSIL TERHADAP PEMERIKSAAN POSITIF PROTEIN URIN - Widyastuti, Rahma (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
PENGARUH PENGENCERAN ASAM SULFOSALYSIL TERHADAP PEMERIKSAAN POSITIF PROTEIN URINÂ Rahma W, S.Si, M.Kes.blue4rahma@gmail.com Prodi D3 Analis Kesehatan UM SurabayaÂ  AbstractThe examination of urinary protein, there are several kinds of methods that can be used is 20% sulfosalysil acid method, stick, acetate acid, bence jones, and Esbach. Sulfosalysil acid method is a non-specific indicator, the method is sensitive to the protein in a concentration of 0.002%. In the laboratory there are health centers that use sulfosalysil acid reagent for examination of urinary protein, in addition to using a stick of urine (strip dye). Reagent consumption is expected to have economic value, it is necessary dilution reagent. Dilution reagent can reduce the level of Corrosiveness to laboratory personnel, the smaller the concentration of reagent concentrations the less the level of corrosive. So it apost prandialears a formulation of the problem in this research is "Are there sulfosalysil acid dilution effect of the positive examination of urinary protein?". This type of research used in writing this paper is an experimental study. The population in this study were patients with positive urine protein urine in hospitals Dr.Soetomo Surabaya in the first week of June 2011. Samples were taken from patients with positive urine protein urine in hospitals Dr.Soetomo Surabaya in the first week of June 2011 were taken randomly . To supost prandialort this research, we used a statistical test friedman test, the results obtained friedman test p = 1.000. So there is no significant difference between giving a urine protein levels sulfosalysil acid 20%, 15%, 10%, 5%, and 1%. In this test, from acid dilution sulfosalysil same statistical results obtained, it is caused by the acid-sensitive protein sulfosalysil in a concentration of 0.002%. Therefore, when the protein concentration <0.002% then sulfosalysil acid can not detect the presence of protein in the urine. To strengthen the results, it can be seen the formation of precipitates. Key word: sulfosalycil acid, urine protein